Portraying Students’ Emotions in English Conversation Clubs at a Colombian University - Anthony Ceron; Norbella Miranda (HOW, 2023)
Emotions are ubiquitous and permeate all aspects of human life, including language learning. However, little attention has been paid to emotions in the ELT curriculum, let alone in the design and implementation of conversations clubs. In this article, we share the qualitative results of a mixed-method study on students’ emotions while participating in a conversation club at a public university in Colombia. Findings show an ample range of students’ emotions, factors commonly associated with these emotions such as academic load and personal life, and the connections of emotions with students’ language learning processes. This study identifies how emotions can facilitate or interfere with language learning, highlights the importance of emotions in the development of oral skills in the context of conversation clubs, and contributes to the understanding of the language learner from a holistic perspective in the field of Applied Linguistics.